Inhibition of galectins in cancer: Biological challenges for their clinical application - Laderach, Diego José; Compagno, Daniel (Frontiers in Immunology, 2023)
Galectins play relevant roles in tumor development, progression and metastasis. Accordingly, galectins are certainly enticing targets for medical intervention in cancer. To date, however, clinical trials based on galectin inhibitors reported inconclusive results. This review summarizes the galectin inhibitors currently being evaluated and discusses some of the biological challenges that need to be addressed to improve these strategies for the benefit of cancer patients.